Photoelectrochemical water oxidation using hematite modified with metal-incorporated graphitic carbon nitride film as a surface passivation and hole transfer overlayer - Jeon, Tae Hwa; Park, Cheolwoo; Kang, Unseock; Moon, Gun-hee; Kim, Wooyul; Park, Hyunwoong; Choi, Wonyong (Elsevier BV, 2024)
Hematite (α-Fe2O3) is renowned as a promising photoanode for water oxidation, even though it displays poor photoconversion efficiency. In this study, ∼5 nm-thick graphitic carbon nitride (g-C3N4; CN) and metal-incorporated CN (M-CN; M = Ag, Fe, Co) films are uniformly deposited on hematite via a facile one-step evaporation method. Herein, the Co-CN layer leads to the highest photoelectrochemical activity with hematite-based photoanode. The subsequent loading of Co-CN layer with oxygen evolution catalysts (FeNiOOH and CoOOH) further enhances photocurrent density to ∼3.5 mA cm？2 and oxygen evolution at > 95 % of Faradaic efficiency over 24 h at E = 1.23 V. Detailed analysis based on spectroscopic and electrochemical measurements demonstrate that the primary role of CN layer is improving the charge separation efficiency by passivating the hematite surface. Then the incorporated metals contribute to reducing charge transfer resistance and thereby mediating hole transfer to interfacial water.